Vizualni jezik predstavitve prostora - ovira ali stičišče? - Zupančič-Strojan, Tadeja (Urbani izziv, 2003)
The article deals with techniques of representation of architectural and urbanistic ideas about space and its changes. It delves into the communicationprocess between co-creators of space and points out the issue of different understanding of visual representation techniques that stem from different levels in capabilities of visual expression and understanding of visual messages. The issue of ignorance of specifics of professional language is emphasised as a consequence of its habitualness. The presented research checks and analyses the effect of abstract/concrete visual representation and their effectiveness in communicating messages to expert and lay publics. Following the discussion about results, numerous new issues arise, concerning possibilities for narrowing the gap between various publics and finding commonground. Amongst different solutions about improving communication between actors in the creation of space, the article emphasises the potential of permanent education. However the quest is not for improvements in general understanding of visual language, but consequentially to devise ways, modes and their positive consequences on the cultural environment and spatial culture.
Keywords: architecture; arhitektura; arhitekturni prostor; communication; javnost; komuniciranje; odnosi z javnostmi; prostor; urbanism; urbanizem; vizualne komunikacije